Effects of Calcination Conditions of Locust Bean Pod on The Mechanical Properties of Locust Bean Pod Ash High-Strength Concrete - Anum, Iorwuese; Abdullahi, Umar; Johari, Megat Azmi Megat; Isa, Felix Nkapheeyan (UI Scholars Hub, 2025)
Locust Bean Pod Ash (LBPA) is produced from the calcination of Locust Bean Pod (LBP), an agricultural waste of the African locust bean tree (Parkia biglobosa). This study evaluated the use of LBPA obtained through controlled calcination and open burning as a supplementary cementitious material (SCM) in high-strength concrete (HSC). Cement was replaced by LBPA at 5%, 10%, 15%, and 20% by weight using both ashes—LC for ash produced through calcination at 600 °C, and LO for ash obtained through open burning. Slump and strength were assessed, including compressive strength (100 × 100 × 100 mm cubes) and splitting tensile strength (100 × 200 mm cylinders) up to 90 days. The results showed that LC contained 42.81% and LO contained 10.69% combined SiO₂, Al₂O₃, and Fe₂O₃. The 5% replacement level produced the best performance for both LBPA types. At 90 days, LC and LO improved compressive strength by 14.48% (68.8 N/mm²) and 10.48% (66.4 N/mm²), respectively, compared to the control (60.1 N/mm²). Similarly, the tensile strengths of LC05 and LO05 were 6.74% (4.75 N/mm²) and 4.94% (4.67 N/mm²) higher than the control (4.45 N/mm²). The study concludes that both ashes can be used as SCMs in HSC, with 5% and 10% recommended as optimum replacement levels for calcined and openly burnt LBP, respectively.